Trust-Driven Entrepreneurship for Community Well-Being of Refugees and Their Local Hosts. (June 2021) - Baktir, Zeynep; Watson, Forrest
This article explores community well-being (CWB) outcomes of institutional trust (and distrust) through entrepreneurship in the context of a refugee-hosting society in Turkey. Existing studies show the positive relationship between institutional trust and quality of life (QOL) as well as entrepreneurship and QOL in subsistence contexts. This research, however, explores the relationship between institutional (dis)trust and entrepreneurship on a path to CWB with a special emphasis on refugee and local interactions in the marketplace. Three different paths to the QOL of refugees and/or locals are presented, but only two lead to CWB outcomes encompassing both refugees and locals. Consideration of refugees and locals as both consumers and business owners provides perspective on the interplay between social trust and institutional trust in a socio-culturally heterogeneous subsistence context. The article also discusses implications for theory and practice.